Critical Theory and Neoliberalism in Brazil: Annotations about Roberto Schwarz and Francisco de Oliveira - Franco, Renato [UNESP] (Soc Estudios Teoria Critica, 2021)
The purpose of this paper is: a) to examine in general terms how the most relevant theoretical conceptions elaborated by a current of thought called Paulista School of Thought were taken up or developed in a new perspective by Roberto Schwarz, who would have elaborated an original conception based on the Critical Theory of Society of Theodor Adorno and Walter Benjamin; b) to point out how the reflection of Schwarz and the authors of the Paulista School of Thought provided elements (or not) for a critique of Neoliberalism and an understanding of Capitalism as a whole; c) finally, this paper aims to examine an important work by Francisco de Oliveira, a tributary of this type of dialectical thinking. And, at the same, it seeks to highlight how this critical current of thought was exhausted with the dissemination of the Neoliberal wave in Brazil.
Keywords: Paulista School of Thought; Roberto Schwarz; Francisco de Oliveira; critical theory in Brazil; critical theory and neoliberalism in Brazil; criticism of neoliberalism and capitalism in Brazil